PERILAKU PETANI DALAM PENGGUNAAN PESTISIDA KIMIA (Kasus Petani Cabai di Pekon Gisting Atas Kecamatan Gisting Kabupaten Tanggamus) - Eliza, Try; Hasanuddin, Tubagus; Situmorang, Suriaty (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2013)
This research was aimed to analyze: behavior of farmers on chemical pesticides use in chilli crop farming, factors that influence the behavior of farmers in the use of chemical pesticides, and performance of chemical pesticides use by the chilli crops farmers. This research was conducted in Pekon Gisting Atas, Gisting District, Tanggamus Regency. Location of this research was chosen intentionally with the consideration that Pekon Gisting Atas has a number of chilli crop farmers and the circulation of chemical pesticides is more than in other pekon. Census method was used, and there were 33 chilli crop farmers as the research respondents. This research was conducted from October 2012 to May 2013. The methods used in this research were methods of case and direct observation. Descriptive and path analyses were used to analyze data. The results showed that behavior of farmers in the use of chemical pesticides in Pekon Gisting Atas was classified good enough. Factors that influenced the behavior of farmers in the use of pesticides were the farming experience, attitude, and farmers’ household income. The performance of chemical pesticide used by chilli crop farmers was as follows: insecticide, fungicide, bactericide, and herbicide was the types of pesticides widely used to control chilli plant pests and diseases; chemical pesticides was sprayed by farmers on scheduled time regardless of the presence or absence of pests and diseases. Key word: behavior of farmers, chilli, path analysis, pesticides, variability